A value-based multi-criteria decision-making approach towards floating house development: a case study in Hong Kong - Wang, Xinhao; Xu, Shi-Yu; Leung, Mei-Yung; Liang, Qi (Journal of Civil Engineering and Management, 2023)
This study aims at investigating the cost-effectiveness of developing a new type of house, the floating house, as a solution to land scarcity in metropolitan coastal cities. Under value management framework, the “function analysis system technique” diagram was established to identify the functions of land-based and floating houses. Participants with different backgrounds shared their views through the two designed questionnaires, assisting in determining the cost allocation and functional performance levels of the houses. Fuzzy set theory was utilized to convert the collected professional knowledge and public opinions into numerical measurements. The obtained function values disclosed that, despite weaknesses in the conventional living and structural issues, the floating house still shows competitiveness and opportunities in customer attraction, environmental sustainability, and encouraging local tourism. This paper offers the evidence and reference to both practitioners and governments seeking for a better value of the money they invest in future floating house projects.